Identificación de un plan de negocios para la exportación de lencería femenina a Estados Unidos (Miami Florida, los Ángeles California y Nueva York Nueva York, Estados Unidos) (2020)
The Zadquiel brand made the identification of a business plan for the export of women's lingerie to the United States (Miami Florida, Los Angeles California and New York New York, United States). in which all the factors involved in an export process were analyzed, stories such as the analysis of the market in which a detailed background of the behavior of the US market and the generation of the impact that women's lingerie products will have. On the other hand, describe the export process which will be carried out, analyzing the best routes and means of transport for the shipment of exports abroad; In the process of selecting and choosing the logistics operators, we also analyze the hourly frequency with which they operate and the operators of these favor the process of log.